Assessing the Relationship between Training Environment and Training Effectiveness in Institut Kajian dan Latihan Integrasi Nasional (IKLIN) Department of National Unity and Integration (JPNIN), Prime Minister Department - Ismail, Zakaria (2010)
This study attempt to evaluate the training effectiveness provided by Institut Kajian Dan Latihan Integrasi Nasional (IKLIN) organised by Jabatan Perpaduan Negara Dan Integrasi Nasional (JPNIN). This study also identify the influencing factors that effect the training affectiveness, that is training environment. Adopted Questionnaires were used for data Collection. Out of 100 participants, 75 respondents returned their questionnaire, making the respons rate of 75 percent. Data was processed and analyse using SPSS. Appropriate data analysis technique were used, both for descriptive and infrential analysis. Findings show that respondents perceived that training environment provided Institut Kajian Dan Latihan Integrasi Nasional (IKLIN) are good especially on their ability in task involvemet. Findings also revealed that training environment is significantly assosiated and influenced the training efectiveness. Suggestion for future research were made at the section of this study.